Mitigation of Occupational Health Safety and Environmental Risk in Construction Projects on The North Coast of Java - Hardiyansyah Lubis, Gilang; Alfionita Pebriani, Cindy; Maulana, Deni (Pelopor Publikasi Akademika, 2025)
In Indonesia, the construction industry sector in the last three years has grown rapidly with increasing infrastructure development in Indonesia. This must be supported by the availability of competent human resources and good supervision of workers. This research focuses on mitigating K3L risks in coastal development projects, where complex environmental factors and operational hazards increase the potential for accidents and environmental damage. The method used in this study is a survey method combined with a research study approach. Data collection was carried out using questionnaires distributed to 30 respondents involved in construction projects along the North Coast of Java. The collected data was analyzed using the Statistical Package for the Social Sciences (SPSS) and the Analytical Hierarchy Process (AHP) to identify, measure, and prioritize risks. SPSS was employed to test data reliability, validity, correlation, and regression, while AHP helped determine risk rankings and the consistency of the assessment. The results reveal that environmental factors pose the highest risk (0.67), followed by equipment (0.26) and human factors (0.07). The study highlights the importance of integrating comprehensive K3L strategies to minimize risks and improve project efficiency. This research offers a structured framework for construction companies to implement more effective safety measures, contributing to safer working environments and more sustainable coastal infrastructure development.